TRADITION OF KOREAN LANDSCAPE. ITS HISTORIC PERSPECTIVE AND INDIGENIZATION - LEE, Hye Seung (International Journal of Korean Humanities and Social Sciences, 2016)
This paper aims to provide general presentation of Korean landscape painting with historic consideration. Some Korean elements of landscape were introduced in the early 5th century, and since the 7th century, mountains have become an important theme in the formation of the image space. From the 10th to the 17th centuries, the Korean landscape developed under Chinese rule. However, in the early 18th century a new painting trend – “Koreanization of the Korean landscape” – appeared and there also had emerged the folk landscape style. Furthermore, in the contemporary Korean landscape there are various attempts towards the search for one’s own artistic vision.